Penerapan Cloud Computing dalam Menunjang Pembelajaran - Simanjuntak, Pastima; Handoko, Koko; Zetly, Sri; Elisa, Erlin (PUAN INDONESIA, 2025)
As a result of the Industry 4.0 revolution, digital and internet technology are now considered to be at the forefront of technology; cloud computing is one of its components. Cloud computing is a method of using the internet to access various services. Some examples of daya include applications such as data storage, servers, databases, networks, and lunak perangkat. As opposed to storing a large number of files on a hard drive or locally on a computer, cloud-based storage enables you to store files as long as you have access to the internet. Cloud computing is a popular option because it offers many benefits, such as reduced costs, increased productivity, speed, efficiency, performance, and security. As a result, many businesses use the cloud to store data. The purpose of the pengabdian activities at PKBM Sahabat Cendikia Batam is to use cloud computing to enhance education.